Population dynamics of two species of leafhoppers of the genus Empoasca Walsh, 1862 (Hemiptera:Auchenorhyncha: Cicadellidae) on soybean in Rajasthan and their morphological characterization - Meena, A. K.; Nagar, R.; Swaminathan, R.; Viraktamath, C. A. (ENTOMON, 2017)
Population dynamics of jassids infesting soybean studies in Rajasthan, India revealed that the jassids comprised of two species in the genus Empoasca [Empoasca terminalis Distant andÂ Empoasca spirosa Dworakowska & Viraktamath]. The highest mean population of jassids was recorded during last week of August in 2015 (43.50 jassids/5 plants) that evinced a significant positive correlation with the mean atmospheric temperature (r = 0.58). During kharif 2016, the maximum population was recorded in the third week of September (30.50 jassids/5 plants) that exhibited a significant positive correlation with the mean atmospheric temperature (r = 0.62), but significant negative correlation with the mean relative humidity (r = - 0.71). Morphological characterization of the two species of Empoasca is given, besides reporting the occurrence of both leafhoppers for the first time on soybean from Rajasthan. A key to distinguish these two species has also been presented.